Possible Role of Leptin in Atopic Dermatitis: A Literature Review - Carlos Jiménez-Cortegana (MDPI AG, 2021)
Atopic dermatitis (AD) is the most frequent chronic inflammatory skin disease, and its incidence has been rapidly increasing in developed countries in the last years. AD presents a high degree of heterogeneity due to biases and confounding factors such as age range, sex, or ethnicity. For those reasons, the search for new biomarkers is crucial. At the same time, obesity, which is a global health problem, has also increased over the years. It has been associated with many pathophysiological states, including skin diseases such as AD, mostly in childhood. Obesity promotes a low grade inflammation driven by many different cytokines and adipokines, including leptin, which has a key role in many other diseases due to its pleiotropic effects. Leptin also has a role in both skin and allergic diseases very related to AD. Thus, this adipokine could have an important role in the pathogenesis of AD, especially in its chronicity. Despite the limited literature available, there is some evidence that leads us to consider leptin as an important adipokine in this skin disease. For this reason, here we have reviewed the role of leptin in the pathophysiology of AD.